Detailed Characterization of Surface Ln-Doped Anatase TiO2 Nanoparticles by Hydrothermal Treatment for Photocatalysis and Gas Sensing Applications. Issue 1806 (2015) - Rahman, Rezwanur; Anderson, Sean T.; Dey, Sonal; Mayanovic, Robert A.
ABSTRACT: Nanostructured anatase TiO2 is a promising material for gas sensing and photocatalysis. In order to modify its catalytic properties, the lanthanide (Ln) ions Eu 3+, Gd 3+, Nd 3+ and Yb 3+ were precipitated on the surface of TiO2 nanoparticles (NPs) by hydrothermal treatment. Results from Raman spectroscopy and X-ray diffraction (XRD) measurements show that the anatase structure of the TiO2 nanoparticles was preserved after hydrothermal treatment. SEM and TEM show a heterogeneous distribution in size and a nanocrystallite morphology of the TiO2 NPs (∼ 14 nm in size) and EDX confirmed the presence of the Ln-ion surface doping after hydrothermal treatment. An increase in photoluminescence (PL) was observed for the Ln-surface-doped TiO2 NPs when measurements were made in forming gas (5% H2 + 95% Ar) at 520 °C. In contrast, the PL measurements made at room temperature did not show any noticeable difference in forming gas or in ambient air. Our temperature-dependent PL results obtained in different gas environments are consistent with modification of oxygen-vacancies and hole-defects due to a combination of hydrothermal treatment and surface Ln-doping.